Physical characterization of granular components used in road construction - Arias García, Pablo Andrés (2016)
In this work we characterize the granular matter that constitutes the standard material employed in road construction. We measure parameters such as: size distribution, flatness and elongation ratios, hardness, stability angles and compactness. All these parameters are measured as a function of grain sizes. Once this information is obtained, we correlated it to describe each granular size family and draw some conclusions on the expected behavior for future application to rheological tests. © 2009 American Institute of Physics.